PENGARUH ADVERSITY QUOTIENT DAN KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA KELAS X SMAN 4 BUKITTINGGI - Riska Gustia; Dessi Susanti (Jurnal Ecogen, 2018)
The purpose of this study is to analyze the influence of adversity quotient and readiness on the result of study. This study is a descripive and assocciative research. The population of this study are all class X students of SMAN 4 Bukittinggi. The analytical method that is used is multiple regression analysis by using SPSS 19 version program This study shows that 1) adversity quotient and readiness simultaneously significants on the result of study of students at economics subject on class X students of SMAN 4 Bukittinggi 2) adversity quotient significants on the result of study of students at economics subject on class X students of SMAN 4 Bukittinggi 3) readiness significants on the result of study of students at economics subject on class X students of SMAN 4 Bukittinggi  Keyword: adversity quotient, readiness, result of study